Internationally recruited nurses from India and the Philippines in the United Kingdom: the decision to emigrate - Maben Jill; Alonso-Garbayo Álvaro (BMC, 2009)
Abstract Background The United Kingdom has recruited nurses from countries with a reported surplus in their nursing workforce, such as India and the Philippines. However, little is known about the decision to emigrate made by nurses from these countries. One theory suggests that individuals weigh the benefits and costs of migration: the push and pull factors. This paper challenges the restricted economic focus of this predominant theory and compares the diverse motivations of nurses from different countries as well as those of nurses with previous migratory experience and first-time migrants. Methods This research was undertaken in a National Health Service acute trust in London by means of a qualitative interpretative approach. Data were collected through face-to-face longitudinal and cross-sectional interviews with internationally recruited nurses from India (n = 6) and the Philippines (n = 15); and analysis of their narratives was used to generate data about their expectations and experiences. Data were analysed by means of a framework approach that allowed for intra-case and cross-case analysis. Results From an individual perspective, nurses in this study reported economic reasons as the main trigger for migration in the first instance. Yet this doesn't entirely explain the decision to move from previous migratory destinations (e.g. Saudi Arabia) where economic needs are already fulfilled. In these cases migration is influenced by professional and social aspirations that highlight the influence of the cultural environment - specifically some religious and gender-related issues. Family support and support from migratory networks in the country of origin and destination were also important elements conducive to and supportive of migration. Nurses from India report coming to the United Kingdom to stay, while Filipina nurses come as temporary migrants sending remittances to support their families in the Philippines. Conclusion This study shows the diverse motivations of nurses from different countries and with different migratory backgrounds and provides evidence that factors other than economic factors influence nurses' decision to emigrate. This information can help developing countries increase retention of this essential and often scarce resource and can also help the United Kingdom's National Health Service to improve the experience of internationally recruited nurses and therefore increase their retention in the United Kingdom.